The criterion of dependency in civil law : Comparative Study - Yousif, Fawaz; Sultan, Hameed (Journal of Legal Sciences, 2022)
The dependency means the existence of a subordinate to whom a dependant is attached and extends his judgment to him, being and nothing, Dependency has elements that must be available to achieve the dependency relationship, which is the existence of dependent and master with a link join the first to the second, and dependency may be between two obligations, between two rights, or between two things, And we suggested the nature of the obligation as a criterion for verifying the existence of dependency , Which requires the subordinate's attachment to the master with a permanent fateful bond so that one of them does not separate from the other, for the existence of the follower is associated with the existence of the master and it does not expire except with the expiration or demise of the master, and thus the follower follows him in his judgment.